Utility of Toll-Free Interactive Voice Response System (IVRS) Helpline under National Oral Health Program (NOHP) - A Cross-Sectional Hospital Based Study - Utkal K. Mohanty; Swapna Sarit; Gaurav Sharma; Jayanta K. Dash (Indian Journal of Dental Research)
Background: India launched the National Oral Health Program (NOHP) in the year 2014-15 to support the states for improved oral healthcare delivery and reduce the burden of oral diseases. The toll-free Interactive Voice Response System (IVRS) with contact number 1800112032, was initiated to deliver oral health-related information to users and guide them for proper treatment on World Oral Health Day on 20th March 2017. There is scarcity of data regarding the utility and perception of users about IVRS. This study will try to underpin the factors, which can be useful in further improvement in the helpline operation. Aims: To assess the perception of patients regarding the use of the existing IVRS helpline under NOHP for oral health-related information. Methods and Material: The present cross-sectional nonclinical dental survey was carried out among 980 adults aged 18 years and above visiting SCB Dental College and Hospital, Cuttack, Odisha. Statistical Analysis: Descriptive statistics with proportions were calculated and Chi-square was computed, P < 0.05 was considered significant for all statistical inferences. Results: None of the participants were aware of the existence of the toll-free helpline number of NOHP. A significantly higher proportion of female participants responded that IVRS was useful in getting unassisted oral health-related information (P < 0.001). Conclusions: The services of IVRS remains underutilised by the general population due to lack of awareness regarding its existence. The IVRS helpline can be readily accessed for information regarding common oral diseases, immediate home-based care and when to approach for professional help for the common oral health issues.